Accelerating implementation of the African Union Climate Change and Resilient Development Strategy and Action Plan (2022-2032) through the Nairobi Declaration commitments - Trautman, Sabrina; Chevallier, Romy; Gosling, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The African Heads of State and Government gathered for the inaugural Africa Climate Summit in Nairobi, Kenya, from 4th to 6th September 2023. The Summit sought to launch a new climate ambition for Africa and to invite supportive partnerships to pursue the continent’s climate-resilient, low emissions development pathways. The Summit focused on climate change and development in Africa, and the need for improved global investment in climate action. African countries were able to detail their plans and investment needs, and push for reform of international financial architecture. Importantly, the Summit mobilised support for the implementation of sustainable development and climate change related continental programmes and policies. It concluded with the Nairobi Declaration which specifically states the need to accelerate implementation of the African Union Climate Change and Resilient Development Strategy and Action Plan (2022-2032). Many of the commitments and calls to action in the Declaration reinforce those given in the Strategy’s intervention axes, particularly those focused on renewable energy development, green industrialisation and employment creation, and the need for an increase in climate finance, and the restoration and conservation of land-based ecosystems. Although the Strategy is well supported by the Declaration through alignments in core action areas, there needs to be committed financing to support implementation. As such, the focus of the Declaration on climate finance solutions and the new financial commitments pledged at the Summit may provide a chance for African countries to afford the implementation of the commitments and suggested actions thereby progressing their climate resilient development and adaptation agendas.